TEST OF COPPER WIRE DOSE EFFECTIVENESS ON LARVAL MORTALITY OF Aedes Aegypti MOSQUITO IN 2015 - Pristiana Rahayu; Winarko .; Siti Surasri (GEMA LINGKUNGAN KESEHATAN, 2015)
Control of Aedes aegypti mosquito population still leaves problem that needs to be addressed. Theuse of copper wire as an alternative of  larvicide has been studied yet it has not shown asatisfactory result. This is study pure experimental research using research design post test only control group designwith larvae of Aedes aegypti third instar as samples. Methods of data analysis were descriptiveanalysis and analytical analysis.Experiment result shows that based on the success criteria for effective control and safe for health,this research has not found an effective dose of copper wire to kill larvae of Aedes aegyptimosquito that is safe for health for the percentage of larval mortality with concentration of 38.7%Cu was still below 2 ppm.It is recommended that governments and communities use and promote copper wire as analternative larvicide for vector eradication of dengue with predetermined limit of use that is safe forhealth. Further research can be also carried out with media source of water and variety of concentration.